Prescribing Pattern of Antimicrobial Agents in Neonates at Nepalgunj Medical College, Kohalpur, Banke, Nepal - Neupane, Ganesh Prasad; Rai, Maya; Dhami, Dabal Bahadur; Singh, Ritesh (Journal of Nepalgunj Medical College, 2017)
Introduction: Neonates are most vulnerable to infections due to poor immune system leading to high morbidity and mortality, which justifies early diagnosis and prompt treatment with antibiotics. Antibiotics are the most frequently used drugs in Neonatal Intensive care units. Aim and Objective: The objective of present study was to identify the pattern of use of antimicrobial agents in neonates at the neonatal intensive care unit (NICU) of NGMC. Materials and Methods: A hospital-based, retrospective study (prescription audit) was conducted over a period of 5-month duration at Nepalgunj Medical College by reviewing case records of NICU. Data were collected and analyzed. Results: A total of 150 case records were reviewed and were included in the study. Out of the 150, Neonates 86 (57.33%) were male babies and 64 (42.67%) were female babies. Maximum number (72.66%) neonates admitted to NICU were of low birth weight and most common reason for NICU admission was neonatal septicaemia. The majority of neonates (68.67%) received 2 antimicrobial agents (AMAs), 21.33% received 3 AMAs and average number of antibiotic per case was 2.44. The most commonly prescribed antimicrobial agent was Cefotaxime (58.66%), followed by Amikacin (48%), Ceftriaxone (32%). In fixed dose combination Piperacillin + Tazobactum (28%) was most commonly prescribed. All of the antimicrobial agents were prescribed by brand name. Conclusion: Measures need to be undertaken to encourage physicians to prescribe AMAs in generic names to minimize health care cost. Present study suggests that Antibiotics policy to be framed & periodically reviewed: to reduce unnecessary use of antibiotics and associated problems.